“I'm Kinda Stuck at Home With Unsupportive Parents Right Now”: LGBTQ Youths' Experiences With COVID-19 and the Importance of Online Support - Fish, Jessica N.; McInroy, Lauren B.; Paceley, Megan S.; Williams, Natasha D.; Henderson, Sara; Levine, Deborah S.; Edsall, Rachel N. (Journal of adolescent health, 2020)
LGBTQ youth are a population who experience unique stressors. This study investigated their experiences with the COVID-19 pandemic via Q Chat Space—a national online chat-based support program. Transcript data from 31 synchronous, text-based chats collected during the onset of state-based “social distancing” ordinances in Spring 2020 were analyzed. While encountering COVID-19–related stressors likely to be experienced by youth generally, participants' experiences were concomitantly imbued with LGBTQ-specific intrapersonal, interpersonal, and structural challenges. Difficulties included maintaining mental health, being isolated with unsupportive families, and loss of in-person identity-based socialization and support. Findings highlight the importance of synchronous, text-based online platforms to enable LGBTQ youth to feel safe to seek support while at home. Given the potential for long-term physical distancing, concerted efforts are required to provide necessary resources and support for LGBTQ youth during the COVID-19 pandemic.